Relationship Between Neuroticism Type Of Personality Academic Procrastination In Dawan's Ethnic Students In The District Of South Central Timor - Syaban Baun; Marylin S. Junias; Juliana M. Y. Benu (Journal of Health and Behavioral Science, 2020)
This study aims to find the relationship between neuroticism personality types and academic procrastination among ethnic Dawan students in South Central Timor Regency. This type of research is quantitative research. The population was students of the STKIP Soe with Dawan ethnicity who were taken based on predetermined criteria, while the sampling used was accidental sampling on 85 students Dawan ethnicity. Procrastination is a deliberate delay in an important task, done repeatedly on purpose and causes feelings of discomfort in a subjective way. Subjective cultural stereotypes to the East Timorese ethnic group, the people are anxious, jealous, believe in myths, and selfish. Such stereotypical traits can generally be observed in people with the neurotic personality type. Data were collected using a scale and processed and analyzed using the Pearson Product Moment correlation statistical test. The results showed that there was a significant relationship between the Neuroticism personality type and Academic Procrastination where the Pearson Coorelation value = 0.238 with a significance value of 0.029 (ƿ <0.05)